2018
DOI: 10.1002/hbm.24023
|View full text |Cite
|
Sign up to set email alerts
|

Reduced corticostriatal functional connectivity in temporomandibular disorders

Abstract: Although temporomandibular disorders (TMD) have been associated with abnormal gray matter volumes in cortical areas and in the striatum, the corticostriatal functional connectivity (FC) of patients with TMD has not been studied. Here, we studied 30 patients with TMD and 20 healthy controls that underwent clinical evaluations, including Helkimo indices, pain assessments, and resting-state functional magnetic resonance imaging scans. The FCs of the striatal regions with the other brain areas were examined with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…A recent study indicated a role of striatum. Patients with TMD show decreased corticostriatal functional connectivity, for example, between ventral striatum and ventral frontal cortices (ACC or anterior insula), which might underpin altered motor control, pain processing, and cognition (He et al 2018). A meta-analysis study suggested that these altered brain networks in patients with TMD are largely in common with those in patients with trigeminal neuropathy (e.g., changes in ACC, insular cortex, prefrontal cortex, and basal ganglia) with some distinct components (e.g., involvement of distinct regions of insular cortex and less involvement of thalamocortical connectivity in TMD; Lin 2014).…”
Section: Central Mechanisms For Craniofacial Muscle Painmentioning
confidence: 99%
“…A recent study indicated a role of striatum. Patients with TMD show decreased corticostriatal functional connectivity, for example, between ventral striatum and ventral frontal cortices (ACC or anterior insula), which might underpin altered motor control, pain processing, and cognition (He et al 2018). A meta-analysis study suggested that these altered brain networks in patients with TMD are largely in common with those in patients with trigeminal neuropathy (e.g., changes in ACC, insular cortex, prefrontal cortex, and basal ganglia) with some distinct components (e.g., involvement of distinct regions of insular cortex and less involvement of thalamocortical connectivity in TMD; Lin 2014).…”
Section: Central Mechanisms For Craniofacial Muscle Painmentioning
confidence: 99%
“…The neurophysiological basis of emotion generation and perception involves a wide range of cortical and subcortical regions (e.g., striatum, hippocampal complex, amygdala, thalamus), which is also known as the fronto-striatal-limbic mood regulation circuit (MRC) ( Anand et al, 2005 ). Neuroimaging studies have found that most brain regions with abnormal neural activity in TMD patients are located in or related to MRC ( Moayedi et al, 2011 , 2012 ; Gerstner et al, 2012 ; Ichesco et al, 2012 ; He et al, 2018 ; Lim et al, 2021 ). However, their relationship with emotional symptoms and the role between pain and emotion remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies have further implicated CNS dysregulation in chronic TMD pain, showing that patients exhibit structural [18][19][20][21], functional [22][23][24][25][26][27][28][29], and neurochemical [28,30,31] alterations involving brain regions associated with pain processing [12,32]. Stimulusevoked functional magnetic resonance imaging (sfMRI) is commonly used to investigate CNS mechanisms underlying pain processing in humans [32].…”
Section: Introductionmentioning
confidence: 99%